PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KOLABORASI - Baiq Daniartya Masullah; Jailani Jailani (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
During the learning process the role of the teacher is very important, the selection of the learning model to be used must be flexible which makes it easier for students to develop the ability to think mathematically. The purpose[Reviewer1] [Bdm2] of this study was to determine the effect of learning mathematics with the numbered heads together (NHT) cooperative model on learning outcomes and to see the effect of the numbered heads together (NHT) cooperative model in improving students' critical thinking skills and collaboration. In this study using Pre-Experimental where Pre-Experimental research only involved one class as an experimental and treatment class. The subjects in this study were students in class VII D at SMP Negeri 6 Praya Timur consisting of 31 students. Data collection techniques in this study used a test consisting of a test instrument and a questionnaire instrument. The test instruments used in this study were basic competence achievement tests (KD) and critical thinking tests, while the questionnaire instruments used in this study were collaboration questionnaires. The data analysis technique in this study was hypothesis testing using a paired sample t-test. The results of the study showed that the average score for achieving basic competence of students at the time of the pretest was 51.80 and the posttest was 80.73, for the average score of critical thinking during the pretest was 24.09 and the posttest was 67.58, while the score the average collaboration obtained by students during the pretest was 73.008 and the posttest was 76.875. So it was concluded that using the numbered head together (NHT) cooperative model was able to improve student learning outcomes as seen from basic competencies, and was able to support students' critical thinking skills and student collaboration.